2007
DOI: 10.1007/s11116-007-9136-6
|View full text |Cite
|
Sign up to set email alerts
|

Urban form, travel time, and cost relationships with tour complexity and mode choice

Abstract: Urban form, Travel time, Mode choice,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
157
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(171 citation statements)
references
References 20 publications
9
157
0
5
Order By: Relevance
“…This paper contends that while policy efforts have coincided with higher levels of bicycle use in Berlin, there are a number of other causal factors at play. This analysis resonates with the work of Maddox (2001) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Cost is recognised as important in transport choice (Frank et al, 2008) and Maddox (2001) cites economic shifts as influencing the growth in cycling in Germany since the 1970s.…”
Section: Re-examining Berlin's Cycling Transitionsupporting
confidence: 78%
“…This paper contends that while policy efforts have coincided with higher levels of bicycle use in Berlin, there are a number of other causal factors at play. This analysis resonates with the work of Maddox (2001) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Cost is recognised as important in transport choice (Frank et al, 2008) and Maddox (2001) cites economic shifts as influencing the growth in cycling in Germany since the 1970s.…”
Section: Re-examining Berlin's Cycling Transitionsupporting
confidence: 78%
“…In addition to self-selection problems, other issues that can possibly confound the relationship between built environment and travel behavior include spatial auto-correlation, inter-trip dependency, and geographic scales (Krizek 2003b;Bottai et al 2006;Chen et al 2008;Frank et al, 2008). Spatial auto-correlation is a problem in geographic analysis, since individuals and firms located in the same spatial unit are likely to be similar in ways not accounted for by their observable characteristics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Self-selection essentially is an individual's decision to live in a particular residential location based on his/her travel preferences (Frank et al 2008), which is counter to the causal direction normally assumed by researchers (from BE to behavior). Cao et al (2006a) concluded that self-selection has more influence on non-motorized trip making than automobile and transit trips.…”
mentioning
confidence: 91%
“…NMT offers many benefits to individuals and the wider community. For example, researchers have found that those traveling more often by non-motorized modes enjoy better physical and mental health (Frank and Engelke 2001 and Litman 2003). Shorter trips and non-motorized trips also reduce a variety of emissions and roadway congestion (see, e.g., Litman [2003] and Rietveld [2001]).…”
mentioning
confidence: 99%